Hand Index - A Forensic Tool for Sexual Dimorphism - Sah, Sanjay Kumar; Jeelani, Bashir Ahmed (Journal of Lumbini Medical College, 2019)
DOI: https://doi.org/10.22502/jlmc.v7i1.272 Introduction: Amongst the various parameters of identification, sex is one of the most important elements. Figuring out hand index from measurement of hand dimensions is a convenient way to determine sexual dimorphism. This study aims to find out sexual dimorphism from hand dimensions, obtain cut off points for male and female and check percentage accuracy of sex determination from hand dimensions in Nepalese population. Methods: The data was collected from 400 asymptomatic, healthy working staff (229 males and 171 females) above 23 years in the department of Forensic Medicine and Toxicology of a tertiary care center of Western Nepal. Measurements of hand length and hand breadth were taken using standard instruments and hand index was calculated therefrom. Results: The mean (±SD) right hand lengths for male and female were found to be 17.87 cm (±0.87) and 16.93cm (±0.58) respectively. The mean (±SD) left hand lengths for male and female were 17.85 cm (±0.86) and 16.97 cm (±0.56) respectively. The average hand breadth for male was 1.00 cm greater for right hand and 0.96 cm greater for left hand as compared to female hand breadth. Differences in length and breadth of hands for both sexes were statistically significant (p<0.001) with no statistically significant difference of hand dimensions in the same sex. Cut off point for right hand index was found to be 42.32 cm and for left hand, 42.30 cm. Conclusion: Hand dimensions and hand index can be reliably used to determine sex in medicolegal cases, especially where isolated hand is obtained.